The Relationship between Anemia Status and Newborn Weight Outcomes - Ariyani Lutfitasari; Sherkia Ichtiarsi Prakasiwi; Fitriani Nur Damayanti; Lia Mulyanti (Jurnal Kebidanan, 2023)
Background: Anemia has been a crucial contributor to adverse pregnancy outcomes such as premature birth, low birth weight (BBLR), small for gestational age (IUGR), as well as delivery by cesarean section. Methodology: The method used is an analytical survey method with a cross-sectional approach. The population in this study is all mothers who gave birth in the working area of the Bangetayu Health Center in Semarang City from September 2021 to September 2022. The sampling technique uses Consecutive Sampling. Results: Chi-Square test results, there is a relationship between Anemia Status and Newborn Weight Outcomes at Bangetayu Health Center Semarang City (p-value = 0.001). Conclusion: Hemoglobin levels in pregnant women should be observed even from the first trimester of pregnancy to avoid a higher risk of adverse pregnancy outcomes.